The soccer fields in Morelos, Mexico: a socialization space for “futboleras” - Ramírez, Tania Alejandra (2020)
Private football pitches and non-professional women’s football leagues are places that wo- men have fought for, to be able to build spaces of self-care, fun, and socialization. The league contains a metaphorical sense as it relates various aspects of their lives through the experien- ce of “passion” for soccer.